The problems of research of stochastic and dynamic properties of system with Lennard-Jones potential by means of molecular dynamics method - Golovnev, Igor Fedorovich; Golovneva, Elena Igorevna; Fomin, Vasiliy Mikhailovich (Computational Continuum Mechanics, 2013)
Correspondence analysis is carried out to compare the numerical results obtained by the molecular-dynamics method and the basic dynamic concepts of fundamental theories (classical mechanics, statistical physics, and thermodynamics). As an example problem, we study the properties of the system of argon atoms described by a Lennard-Jones interaction potential. The invariant features of phase trajectories with respect to time-impulse inversion are formulated in terms of the algebraic modification of von Neumann classical mechanics. Application of high-accuracy numerical schemes to molecular-dynamics simulations yields the results that obey the symmetry criterion with respect to pulse inversion and the reversibility criterion of trajectories with respect to time reversion. It is shown that these results are locally stable in the Lyapunov sense over the time interval up to 100 ps.